Analysis of Factors Influencing Success in Badminton through the Integration of Performance, Social, and Survey Data Using Artificial Intelligence Methods - Albuzyara, Raafat Ahmed Sabrl; Moharramzadeh, Mehrdad; Naghizadeh Baghi, Abbas; Azizian Kohan, Nasrin (Journal of Foresight and Health Governance, 2025)
The objective of this study is to analyze the factors influencing success in the sport of badminton by integrating performance, social, and survey data and to identify the key drivers of the development of this sport using artificial intelligence methods. This applied study was conducted using a qualitative approach and a descriptive phenomenological method. The study population consisted of university faculty members, coaches, professional and semi-professional badminton athletes, and sports analysts, from whom 26 participants were ultimately selected as the sample. Data were collected through semi-structured interviews and subsequently analyzed and coded. The validity and reliability of the data were ensured based on the criteria of credibility, transferability, dependability, and confirmability. The results indicated that success in badminton is influenced by a combination of factors, including individual and technical performance, athletic motivation and commitment, social and team interactions, the utilization of technology and data analytics, environmental conditions and training facilities, as well as competitive decision-making and strategic planning. The application of performance data and artificial intelligence technologies enables continuous performance monitoring, technical improvement, intelligent planning, and the identification of the principal drivers of success. This study demonstrates that the integration of performance, social, and survey data using artificial intelligence methods provides a deeper understanding of the factors influencing success in badminton and facilitates the design of optimal training programs to enhance athletes’ performance. The findings offer significant practical implications for improving training quality, identifying talent, and predicting performance, and can serve as an effective guide for coaches and sports organizations.